Variability of dry mass as a fundamental biological property demonstrated for the case of Vaccinia virions - Bahr, G.F.; Foster, W.D.; Peters, D.; Zeitler, E.H. (Biophysical journal, 1980)
The dry mass of individual vaccinia virions, as an example of a presumably uniform biological population, prepared in different lost at the Institute for Tropical Hygiene in Hamburg, was tested for variability by quantitative electron microscopy. A value of 5.26 X 10(-15) g for the median weight of the particle was calculated from 7,300 determinations. By assessing the variability of polystyrene latex spheres, which were used as mass standards, we demonstrated that the variability of dry mass of vaccinia virions is fivefold greater than the variability (standard) introduced by the method for determining mass. It was concluded that while genetic control in a presumably homozygous virion is strict with respect to quality, quantity of viral components (other than DNA) varies in fashion that can be aptly described by a log-normal distribution. It is recognized that this observation is empirically supported by the paradigm that any composite biological entity is subject to quantitative variability, the more so the heavier the individual representatives of a species are. In addition, the effects that extractions and staining have on the dry mass of vaccinia are reported, as well as is the median for the dry mass of other strains of pox viruses.